Capital social, redes sociais e empreendedorismo em Moçambique – Análise de Casos de Jovens Empreendedores - Cossa, G. (Revista Comunicação e Sociedade, 2018)
This paper analyses how some young Mozambican entrepreneurs obtained success, using their networks of contacts and other non-economic resources, which can be classified as “social capital”. This social capital allowed them to achieve recognition and ensure the sustainability of their businesses. To this end, qualitative research has been carried out, based on six case studies of young entrepreneurs selected from different provinces of Mozambique. The research concluded the following: first, social networks are not spontaneous; second, strong ties had a significant influence in the initial stage of the venture and weak ties were created along the trajectory of the entrepreneurship, followed by the meaningful strategy and allowing the creation of social capital; third, the entrepreneurs without precedents of political ties or strong influence in the public sector, by their technical capacity, have their own social capital (stock), from the family networks, by means of their entrepreneurial characteristics (profile), recognition of competence (human capital) and motivated by financial and professional independence, business opportunities and personal fulfillment.